HUBUNGAN ANTARA PERCAYA DIRI DENGAN KETERAMPILAN BERBICARA MAHASISWA SEMESTER KEDUA PROGRAM STUDI PENDIDIKAN BAHASA DAN SASTRA INDONESIA - Ni Luh Sukanadi; I Gusti Ayu Putu Tuti Indrawati; Ida Bagus Nyoman Mantra (Bajang Institute, 2025)
Developing speaking skills is the most important element for students in learning a language. However, students face various challenges in perfecting their speaking skills, especially lack of self-confidence. This study uses ex-post facto research with correlation methodology to determine the significant relationship between second semester students' self-confidence and speaking skills. The research sample was second semester Indonesian language and literature study program students selected using a cluster sampling approach plus a lottery system. Data were obtained using research instruments in the form of questionnaires and tests to measure speaking skills. The data obtained were analyzed using descriptive statistics. The results of the data analysis showed that the correlation coefficient of 0.93 indicated that the data was more than 0.05 and had a very good correlation. In other words, the research findings indicate a significant relationship between second semester students' self-confidence and their speaking skills